Nickel-catalyzed electrochemical Minisci acylation of aromatic N-heterocycles with α-keto acids via ligand-to-metal electron transfer pathway - Ding, Hang; Xu, Kun; Zeng, Cheng-Chu (Journal of catalysis, 2020)
[Display omitted] •The first example of Ni-catalyzed Minisci acylation reaction was developed.•This protocol avoids using external chemical oxidants.•A ligand-to-metal electron transfer process was observed. A nickel-catalyzed electrochemical methodology for the Minisci acylation of aromatic electron-deficient heterocycles with α-keto acids has been developed. The reaction is performed in an undivided cell under constant current conditions, featuring broad scope of substrates and avoiding the conventional utilization of silver-based catalysts in conjunction with excess amount of oxidants. Cyclic voltammetric analysis disclosed that a ligand-to-metal electron transfer process may be involved in the generation of the key acyl radicals.